Dual Inoculation with Mycorrhizal and Saprotrophic Fungi Applicable in Sustainable Cultivation Improves the Yield and Nutritive Value of Onion - Jana Albrechtova; Ales Latr; Ludovit Nedorost; Robert Pokluda; Katalin Posta; Miroslav Vosatka (The Scientific World Journal)
The aim of this paper was to test the use of dual microbial inoculation with mycorrhizal and saprotrophic fungi in onion cultivation to enhance yield while maintaining or improving the nutritional quality of onion bulbs. Treatments were two-factorial: (1) arbuscular mycorrhizal fungi (AMF): the mix corresponding to fungal part of commercial product Symbivit (Glomus etunicatum, G. microaggregatum, G. intraradices, G. claroideum, G. mosseae, and G. geosporum) (M1) or the single-fungus inoculum of G. intraradices BEG140 (M2) and (2) bark chips preinoculated with saprotrophic fungi (mix of Gymnopilus sp., Agrocybe praecox, and Marasmius androsaceus) (S). The growth response of onion was the highest for the M1 mix treatment, reaching nearly 100% increase in bulb fresh weight. The effectiveness of dual inoculation was proved by more than 50% increase. We observed a strong correlation (r=0.83) between the growth response of onion bulbs and AM colonization. All inoculation treatments but the single-fungus one enhanced significantly the total antioxidant capacity of bulb biomass, was the highest values being found for M1, S + M1, and S + M2. We observed some induced enhancement of the contents of mineral elements in bulb tissue (Mg and K contents for the M2 and M2, S, and S+M2 treatments, resp.).